Analisis Kandungan Logam Berat (Pb, Hg, Cu dan As) Pada Kerupuk Kemplang Di Desa Tebing Gerinting Utara, Kecamatan Indralaya Selatan, Kabupaten Ogan Ilir - Kiki Agus Ariansya; Kiki Yuliati; Siti Hanggita R.J. (Universitas Sriwijaya, 2012)
The purpose of research was to investigated the heavy metal (Pb, Hg, Cu, and As) content on the kerupuk kemplang (traditional fish cracker) at the North Tebing Gerinting Region, District of South Indralaya, Ogan Ilir Regency.This research was conducted on September until May 2012 the north region Tebing Gerinting, district of South Indralaya, Ogan Ilir regency and Laboratory of Balai Riset dan Standarisasi Industri dan Perdagangan, Palembang.This research used survey method to obtain primary data. The data showed the value of heavy metal content differs, there were fish source (marine fish and fresh water fish), location (in the roadside and in the village), and drying method (with and without rack) and each sample was replicated two times. The parameter of observation were conducted on plumbum (Pb), mercury (Hg), copper (Cu) and arsenic (As).The result of the research revealed that plumbum (Pb) of Kerupuk kemplang with raw material from marine fish and dried in the roadside with rack had value of plumbum 0,0025 mg/kg and in the roadside without rack had 0,0108 mg/kg. Drying on the village with rack had 0,005 mg/kg and without rack had 0,0005 mg/kg. Kerupuk kemplang with raw material from freshwater fish and dried in the rack of roadside had value of plumbum 0,0021 mg/kg and without rack had the value of 0,0055 mg/kg. Drying on the village with rack had 0 mg/kg and without rack had 0,005 mg/kg. Plumbum’s content on kerupuk kemplang still below the threshold were allowed, had the value of 0,3 mg/kg, but it should be able attention because of its heavy metal that could be accumulated in human’s body especially on kidney, heart and brain.